On the use of standard DRK isotherms in Dubinin’s t/F method - Hugi-Cleary, Deirdre; Stoeckli, Fritz (My University, 2000)
It is shown that the adsorption of benzene, carbon tetrachloride, dichloromethane and nitrogen by a typical non-porous carbon black follows the Dubinin–Radushkevich–Kaganer equation. The requirement for temperature invariance is fulfilled, with an average characteristic energy Eo=10.8 kJ mol−1. This expression is compared with the standard isotherms for benzene and carbon tetrachloride at 293 K proposed by Dubinin and used as a reference in the so-called t/F method, which leads to the non-porous surface area of active carbons. It appears that Dubinin’s isotherm contains inconsistencies, which are compensated for internally. Alternative DRK expressions, applicable to different vapours, are therefore proposed. The present study also shows the limits of Dubinin’s method with respect to comparison plots at higher relative pressures.
Keywords: A. activated carbon; C. adsorption; D. microporosity; surface area